Fundamental Based Strategy for Selecting Potential Stocks in the Jakarta Islamic Index - Vidada, Irwin Ananta; Saridawati, Saridawati; Aliudin, Raden Muhammad Tedy; Suprianto, Agung; Sabariah, Etika (SEAN Institute, 2025)
This study addresses the challenge of identifying potential stocks for long-term investment within the Jakarta Islamic Index (JII) amid dynamic market conditions and regulatory changes impacting the capital market. The research aims to develop a systematic approach to stock selection based on fundamental analysis, utilizing the Stockbit application’s Stock Screener feature. The method involves several stages, including defining screening criteria based on market capitalization, profitability, revenue growth, Return on Equity (ROE), Net Profit Margin (NPM), debt levels, and dividend consistency. Stocks are further evaluated through valuation metrics such as Price Earnings Ratio (PER) and Price to Book Value (PBV) to identify potential discounts of over 20% relative to their five-year historical averages. The screening process shortlisted four issuers: KLBF, TLKM, ASII, and UNTR, all of which meet both quality and valuation criteria, and are currently trading at attractive discounts. These findings offer valuable insights for investors, providing a practical framework for initial screening and deeper financial analysis, including examination of the companies’ financial statements and business models. The study concludes that integrating digital tools like Stockbit with fundamental analysis enhances decision-making for investors and suggests further research to explore advanced screening techniques and integration with sharia compliance considerations.